Increasing Student Activeness Through Differentiated Learning - Hastuti, Yulianita; Rahmawati, Ani Frida; Huda, Syaiful (Proceeding International Conference on Lesson Study, 2023)
This research was initiated by the teacher's reflection on the students' activeness in junior high school. During the learning process, it can be seen that the students' activeness of SMP Negeri 3 Jember was low. This research aimed at collecting data and information about students' activeness of the eighth grade students at SMP Negeri 3 Jember by implementing differentiation learning. Classroom action research with a qualitative approach was implemented in this study. The subject of the research was the eighth-grade students at SMP Negeri 3 Jember as many as 31 students. This research was carried out in two cycles. The design of the research consisted of (1) planning, (2) implementing, (3) acting and observing, (4) reflecting. The data were collected through observation techniques. The data were analyzed using the percentage technique. The results of the research showed that there was an increase in students' activeness by 24%. Therefore, the differentiation learning could improve the eighth-grade students' activeness at SMP Negeri 3 Jember.